Two new species of Anthaxia Eschscholtz, 1829 from Spain (Coleoptera: Buprestidae) - Arnáiz-Ruiz, Lucía; Bercedo-Páramo, Pablo (Zootaxa, 2003)
Two new species from Spain are described and illustrated: Anthaxia (Melanthaxia) zarazagai sp. n. and Anthaxia (Melanthaxia) lencinai sp. n. A diagnosis for theirs differentiation from the closest allies A. (M.) carmen Obenberger, 1912 and A. (M.) godeti Gory & Laporte, 1839 is given.